2004
DOI: 10.4067/s0717-95022004000400010
|View full text |Cite
|
Sign up to set email alerts
|

SUBLETHAL DOSES OF MALATHION ALTER MALE REPRODUCTIVE PARAMETERS OF Eisenia foetida

Abstract: SUMMARY:Malathion is an organophosphorate insecticide whose main acute poisonous effect is the inhibition of the enzyme acetylcholinesterase. This pesticide is widely used and has been reported to damage mice spermatogenesis. The objective of this work was to evaluate the toxic risk of malathion, earthworm Eisenia foetida (Annelida, Oligochaeta) like biological model was used and testicles and spermatozoa of animal controls and treaties were analyzed. Earthworms with developed clitellum were used and they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This morula reaches a maximum of 128 germ cells after meiosis due to their synchronous development. Our histomorphological study showed that the spermatogenesis of P. peguana is similar to that in Eisenia fetida (Espinoza‐Navarro and Bustos‐Obregón, ). These morulae have different numbers of cells, which may grow in geometric progression to morulae of spermatogonia, spermatocytes, or spermatids.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This morula reaches a maximum of 128 germ cells after meiosis due to their synchronous development. Our histomorphological study showed that the spermatogenesis of P. peguana is similar to that in Eisenia fetida (Espinoza‐Navarro and Bustos‐Obregón, ). These morulae have different numbers of cells, which may grow in geometric progression to morulae of spermatogonia, spermatocytes, or spermatids.…”
Section: Discussionsupporting
confidence: 63%
“…Sorour and Larink () reported that pesticides could damage spermatozoa by altering the ultrastructure of the cytoskeleton of the cytophore and spermatogonial morula, thereby affecting the normal development of spermatogenesis and spermiogenesis. Espinoza‐Navarro and Bustos‐Obregón () reported that malathion affects tissue disorganization, vacuolization, and the presence of small and hyperchromatic nuclei in spermatogonial morulae indicative of possible apoptosis. This is similar to the findings of El‐Kashoury and Tag El‐Din () who reported that testes of chlorpyrifos‐treated albino rats exhibit degeneration and atrophy of nonfunctional seminal tubules and a marked decline in sperm cells within the lumen of seminiferous tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ejection of sperm seems also to be hindered and therefore a large number of spermatozoa are found in intoxicated worms in spite of a clear effect on sperm production under parathion treatment as discussed by Bustos-Obregón and Goicochea [3]. According to Espinoza-Navarro and BustosObregon [58] malathion also has a direct cytotoxic effect causing coiling of the tail, with increase of metachromasia of the chromatin of the spermatozoa and altering the sperm count…”
Section: Effects On Reproductionmentioning
confidence: 99%
“…Earthworm growth and cocoon production were significantly reduced [36] Malathion (pure) 80.150, 300, 600 mg/kg soil Applied and Environmental Soil Science Espinoza-Navarro and Bustos-Obregón [31] treated Eisenia fetida with organophosphate insecticide malathion and found that malathion decreased the spermatic viability in spermatheca, altering the cell proliferation and modifying the DNA structure of spermatogonia. Sperm count also seems to be a very sensitive marker [42,50], malathion could affect the sperm count, but in addition, its metabolites could affect sperm quality [58].…”
Section: Effects On Reproductionmentioning
confidence: 99%